Coefficient Bounds for Certain Classes of Analytic Functions of Complex Order γ Associated with Cardioid Domain - Bhatti, Aijaz Ahmed; Abdul Wasim Shaikh; Shujaat Ali Shah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
In this paper, new Ma–Minda type subclasses of analytic functions of complex order γ, associated with cardioid domain in the open unit disk , are introduced. The objective of this work is to investigate the first three sharp coefficient bounds and to examine the sharp estimates of the Fekete-Szegö problem for these subclasses.